Forecasting Future Funds for Food Security Projects: A Reflection on Trainings for Frontline Extension Staff on Improved Agricultural Practices in Malawi - Hector M. Malaidza; Robert Strong Jr. (Journal of International Agricultural and Extension Education, 2017)
Eighty percent of the Malawian population depends on agriculture for employment. This commentary is a reflection of a number of training workshops conducted to orient frontline extension staff on improved agricultural technologies. These trainings were conducted by the Technology Transfer Unit (TTU) is under the Department of Agricultural Research Services (DARS) of the Ministry of Agriculture, Malawi. The manuscript contains an analysis across various activities were done before, during, and after a number of technical training sessions. The manuscript presents a detailed picture of processes associated with implementation of the trainings where technical information was shared. The results conceptualize insights of things what was effective, and suggests ways of improving trainings in the future. Therefore, this commentary stresses on the importance of conducting training needs assessments for specific technical groups. The lessons drawn from the analysis are sketched in a general schematic model that can be used for designing, implementing and evaluating future agricultural extension staff trainings to improve food security of Malawians.
Keywords: training; agricultural extension; agricultural technologies; technology transfer